Experience sharing of endoscopy-assisted total mastectomy with and without immediate breast reconstruction - Lin, Yidan; Zhuang, Minxue; Qiu, Hongbin; Chen, Wei; He, Yihui; Zeng, Huanhong; Lin, Mengbo; Zhang, Hui (Frontiers in Oncology, 2025)
ObjectiveTo evaluate safety, efficacy, and aesthetics of endoscopy-assisted total mastectomy endoscope(EATM) with immediate breast reconstruction (IBR).MethodsThis retrospective study analyzed 213 patients undergoing total mastectomy (2020.12–2023.2), stratified into four groups: conventional total mastectomy (CTM, n=128), EATM (n=46), CTM+IBR (n=17), and EATM+IBR (n=16). Operative metrics and patient-reported outcomes (Breast-Q/Scar-Q) were compared (SPSS 26.0, P<0.05).ResultsEATM groups exhibited prolonged operative time compared to CTM (P < 0.05) but demonstrated significant advantages in reduced intraoperative bleeding (median: 50 mL vs. 80 mL), shorter incision length (3.2 cm vs. 8.5 cm), earlier drain removal (5 vs. 8 days), and shorter hospitalization (4 vs. 7 days) (P < 0.05). EATM with IBR (Group D) achieved superior breast tissue preservation and higher patient satisfaction in psychosocial health (Breast-Q score: 78 vs. 65) and scar appearance (Scar-Q score: 8.5 vs. 6.2) compared to conventional approaches (P < 0.05). Complication rates were comparable across groups (9.3% vs. 8.7%, P > 0.05), with only one case of local nipple recurrence and three cases of distant metastasis observed during 27-month follow-up.ConclusionEATM combined with IBR represents a safe and effective strategy for breast cancer management, balancing oncological safety with enhanced aesthetic outcomes. The technique reduces surgical trauma, accelerates recovery, and improves patient satisfaction, particularly in scar concealment. Despite higher costs and procedural complexity, it is recommended for patients prioritizing both curative and cosmetic goals. Further multicenter studies are warranted to validate long-term efficacy and cost-effectiveness.